Improving the Selectivity of ZIF-8/Polysulfone-Mixed Matrix Membranes by Polydopamine Modification for H2/CO2 Separation - Mei, Xueyi; Yang, Sheng; Lu, Peng; Zhang, Yexin; Zhang, Jian (Frontiers in Chemistry, 2020)
Gas separation membranes are essential for the capture, storage and utilization (CSU) of CO2, especially for H2/CO2 separation. But both glassy and rubbery polymer membranes lead a relatively poor selectivity for H2/CO2 separation because the differences in kinetic diameters of these gases are small. The present study establishing the mixed matrix membranes (MMMs) consist of a nano-sized zeolitic imidazolate frameworks (ZIF-8) blended with the polysulfone (PSf) asymmetric membranes. The gas transport properties (H2, CO2, N2, and CH4) of MMMs with a ZIF-8 loading up to 10 wt% were tested, and showing significant improvement on permeance of the light gases (e.g., H2 and CO2). Moreover, the depositional polydopamine (PDA) layer further enhanced the ideal H2/CO2 selectivity, and the PDA modified MMMs approach the Robeson upper bound of H2/CO2 separation membranes. Hence, the PDA post-modification strategy can effectively repair the defects of MMMs, and improved the H2/CO2 selectivity.